Gender aspects in chronic myeloid leukemia: long-term results from randomized studies - Berger, Ute; Maywald, Ole; Pfirrmann, M.; Lahaye, T.; Hochhaus, Andreas; Reiter, Andreas; Hasford, J.; Heimpel, H.; Hossfeld, D. K.; Kolb, H.-J.; Löffler, H.; Pralle, H.; et al. (Leukemia, 2005)
Gender-related aspects in chronic myeloid leukemia (CML) have not been studied well. We therefore analyzed 856 patients with Ph/BCR-ABL-positive CML from the German randomized CML-studies I (interferon α (IFN) vs hydroxyurea (HU) vs busulfan) and II (IFN+HU vs HU alone). The median observation time was 8.6 years. A total of 503 patients (59%) were male. Female patients were older (51 vs 46 years; P<0.0001), presented with lower hemoglobin (11.7 vs 12.5 g/dl; P<0.0001), higher platelet counts (459 vs 355 × 109/l; P<0.0001), smaller spleen size (3 vs 4 cm below costal margin; P=0.0097), a lower rate of additional cytogenetic aberrations (9 vs 15%; P=0.018) and a less favorable risk profile (P=0.036). The transplantation rate was 14% for female (n=48) and 22% for male patients (n=113). Median survival was longer in female patients (58 vs 49 months; P=0.035) mainly attributable to better survival in the low- and intermediate-risk groups and, independent from risk groups, in the HU group. These results were confirmed by matched-pair analyses based on German population data (n=496, 59 vs 45 months; P=0.0006). This is the first analysis of gender aspects in CML using randomized trials. It demonstrates the relevance of analyses of gender differences in CML and in malignant disease at large.
Gesehen am 12.05.2022